2000
DOI: 10.1046/j.1365-2141.2000.02317.x
|View full text |Cite
|
Sign up to set email alerts
|

FLT3 internal tandem duplication mutations in adult acute myeloid leukaemia define a high-risk group

Abstract: Genomic DNA from 106 cases of adult de novo acute myeloid leukaemia (AML) was screened by polymerase chain reaction (PCR) and gel electrophoresis for FLT3 internal tandem duplication (ITD) mutations within the juxtamembrane (JM) domain. FLT3 mutations were detected in 14 cases (13.2%) and occurred in FAB types M1 (4 out of 14 cases), M3 (1 out of 10 cases), M4 (5 out of 37 cases) and M5 (4 out of 11 cases). Sequence analysis of four cases with abnormal PCR electrophoretic patterns revealed in frame duplication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
155
2
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(173 citation statements)
references
References 29 publications
11
155
2
5
Order By: Relevance
“…Many studies indicate that FLT3-ITD confers a poor prognosis in AML patients by increasing relapse risk and reducing survival. [17][18][19][20][21] More recently, increasing evidence suggests that higher FLT3-ITD to wild-type allelic ratios are associated with poor prognosis. 22 In our patients, FLT3 mutation by itself did not impact DFS.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies indicate that FLT3-ITD confers a poor prognosis in AML patients by increasing relapse risk and reducing survival. [17][18][19][20][21] More recently, increasing evidence suggests that higher FLT3-ITD to wild-type allelic ratios are associated with poor prognosis. 22 In our patients, FLT3 mutation by itself did not impact DFS.…”
Section: Discussionmentioning
confidence: 99%
“…14 FLT3-ITD is an independent predictor of poor prognosis and is associated with increased relapse risk after chemotherapy, and decreased disease-free survival and overall survival. 6,8,10,15,16 The clinical significance of FLT3-D835 is still unclear. Some studies have shown that FLT3-D835 is associated with shorter disease-free and overall survival.…”
mentioning
confidence: 99%
“…Recent studies have revealed that activating mutations of RTKs frequently occur in acute myelogenous leukemia (AML) patients. For example, internal tandem duplications (ITDs) of the JM domain of FLT3 (FLT3-ITD) are present in 20-30% of de novo AML cases [4]; and approximately 7% of AML patients possess the D835 mutation, a point mutation in the activation loop of the second kinase domain of FLT3 [4]. These mutations result in constitutively activated FLT3 and its downstream signal pathways, and are associated with elevated blast counts, increased relapse rates and poor overall survival in AML [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%